1976
DOI: 10.1063/1.322361
|View full text |Cite
|
Sign up to set email alerts
|

Switching in polystyrene films: Transition from on to off state

Abstract: Experiments on polystyrene films formed by a glow-discharge technique shows a reproducible bistable switching. Various interpretations are briefly reviewed. It is shown that the resistance of the on state is strictly related to the energy needed by the on-off transition. From the value of this energy it is concluded that the most probable explanation is that the on current takes place along a filamentary path constituted by carbon atoms. A quantitative analysis is made on the basis of the heat balance equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 11 publications
1
49
1
1
Order By: Relevance
“…Nominally homogeneous polymers have been used in MIM devices, including true insulators such as polystyrene [36,37] and acrylates [36] as well as PVK [38] with its active side-group, and conjugated polymers such as thiophene derivatives, [39,40] polybiphenyls, [41,42] poly(spirofluorene), [43] and substituted poly(phenylene vinylene). [44] Combinations of functional components have been explored as potential storage media, most commonly electron donors and acceptors, motivated by the conductive properties of organic charge-transfer complexes.…”
Section: Reviewmentioning
confidence: 99%
“…Nominally homogeneous polymers have been used in MIM devices, including true insulators such as polystyrene [36,37] and acrylates [36] as well as PVK [38] with its active side-group, and conjugated polymers such as thiophene derivatives, [39,40] polybiphenyls, [41,42] poly(spirofluorene), [43] and substituted poly(phenylene vinylene). [44] Combinations of functional components have been explored as potential storage media, most commonly electron donors and acceptors, motivated by the conductive properties of organic charge-transfer complexes.…”
Section: Reviewmentioning
confidence: 99%
“…55,56 One type consists of carbon-rich filaments formed by the local degradation of polymer films. 56,57 The other is associated with metallic filaments that result from the migration of electrodes through polymer films. 58,59 The production of metal filaments for filamentary conduction requires the use of polymers with both coordinating atoms and π-conjugation that can bind to metal ions regardless of the binding sites (side chain or main chain).…”
Section: Filament Conductionmentioning
confidence: 99%
“…In this case the memory effect is attributed to electric field-induced charge transfer between the metal nanoparticles and the small organic molecules. Segui et al (1976) and Henish & Smith (1974) suggested that the switching mechanism (i.e. between the two conductivity states) in their devices is due to the formation of conductive filaments between the top and bottom metal electrodes.…”
Section: Introductionmentioning
confidence: 99%